"I want to keep my North Korean accent": Agency and identity in a North Korean defector's transnational experience of learning English. Issue 1 (26th January 2021) - Park, Eun Sung; Lee, Heekyeong
Abstract : Over the past two decades, a growing number of school‐aged North Koreans have migrated to South Korea. Studies examining their adjustment to South Korean schools have shown that these students face numerous challenges, particularly due to their struggles with English. Such studies have mostly regarded North Korean students as an underprivileged group, often comparing their achievements to those of their South Korean peers. Only a few studies have documented individual learners' narratives on their L2‐learning trajectory, which can offer valuable insights into the transnational experiences that may have shaped their agency and identities across time and space. This paper presents one North Korean defector's personal narratives about his English‐learning experiences in three sociopolitical settings of North Korea, South Korea, and the United States, to examine the role that learner agency plays in shaping and reshaping identities, investments, and aspirations in L2‐learning. Data were collected via three separate interviews over a period of three years. The findings illustrate how the participant was able to utilize his North Korean identity as cultural capital and highlight the importance of learner agency and imagined future self as significant tools for understanding the complexity, multiplicity, and fluidity in L2 learning. Abstract :